Pengaruh Kondisi Sosial Ekonomi Orang Tua terhadap Hasil Belajar IPS Terpadu Siswa - Palupi Hapsari; Siti Maryam Yusuf (Institut Agama Islam Negeri Ponorogo, 2021)
The family environment, especially the parents, is the most important and main dimension. For children's development both physical and psychological development. If the socioeconomic conditions of the parents are good and sufficient. From the results of this simple research, the following conclusions can be drawn: (1) The socio-economic conditions of the class parents 8 SMP Negeri 1 Sambit in the academic year 2020/2021 in general can be said to be in the moderate category, namely with a percentage value of 63%, (2) Learning outcomes in the cognitive domain of Integrated Social Studies subjects students grade 8 SMP Negeri 1 Sambit in the academic year 2020/2021 general it can be said that the cognitive learning outcomes of Integrated Social Studies subjects are grade 8 students of SMPN 1 Sambit is in the medium category, namely with a percentage value of 70%, (3) the socioeconomic conditions of the parents are influential significant.for the results learning in the cognitive realm SMP Negeri 1 Sambit year 2020/2021 school year is indicated by a value because the significance value is 0.000 <0.05, which means that it fails to reject H0.